(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: In most of the patients with chronic granulating wounds split skin grafting is the preferred option for coverage of the wounds. Split skin grafts may be applied directly on the granulation tissue or it may be applied after complete removal of granulation tissue. Opinions are divided on this issue. Objectives: To compare the skin take between the split thickness skin grafting on chronic wounds after removal and without removal of granulation tissue in the same patient. Methods: This is a longitudinal type of follow up and comparative study and was carried out in the Department of Plastic Surgery of Dhaka Medical College Hospital, Dhaka between the periods of January 2008 up to December 2009. The study population included the patients with chronic wounds attending the Department of Plastic Surgery of Dhaka Medical College Hospital and in the Plastic Surgery Department of Combined Military Hospital, Dhaka. In this study a total of 57 patients with clinically non infected chronic granulating wounds requiring skin graft were selected. Among which 50 patients were from Dhaka Medical College Hospital and 7 patients were from Combined Military Hospital, Dhaka. In the same patient wounds were divided into Group A and B. In Group A granulation tissue were removed before skin grafting and in Group B the granulation tissues were not removed before skin grafting and skin graft was applied directly on the granulation tissue. 49 JAFMC Bangladesh. Vol 9, No 2 (December) 2013 Results: In the final skin take assessment it was found that in Group A, 49 (86.0%) patients had a take between 91-100% and 8 (14.0%) patients had a take between 81-90%. None of the patients in this group had a take <80%. In Group B, 30(52.6%) patients had a take between 91-100% and 18(31.6%) patients had a take between 81-90%. There were 9 (15.8%) patients who had a take of <80% and among them 02 patients had a take <70%. Statistically this was significant. Conclusion: Whenever the granulation tissue is removed, the recipient bed has a better chance of skin take as far as infection is concerned. But it must be ensured that haemostasis is achieved before application of the graft. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21826 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013